PENGELOLAAN LINGKUNGAN MELALUI GERAKAN BERSIH SAMPAH DI LINGKUNGAN RUMAH ADAT MEKONGGA, KABUPATEN KOLAKA - Tendrita, Miswandi; Alonemarera, A.S.; Ernawati, Ernawati; Sari, Tri Maniarta; Saparuddin, Saparuddin; Maretik, Maretik; Erfina, Erfina; G.P., Sartika (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
The Mekongga traditional house is one of the traditional houses in Southeast Sulawesi which is located in Kolaka Regency. The location of the Mekongga traditional house is next to the Khaera Ummah Kolaka Mosque which is one of the icons of Kolaka Regency. The location of the Mekongga traditional house is also close to Mandra Beach which of course attracts visitors to come to visit while relaxing. As a tourist destination, tourists are required to maintain cleanliness in the environment of the Mekongga Traditional House. The purpose of this service activity is to commemorate Waste Awareness Day on February 28 as well as efforts to manage the environment so that it is clean from waste. The method used is the method of observation and the method of participation. This activity was attended by 29 people consisting of lecturers and students. The trash that is cleaned is dominated by plastic waste in the form of straws, drink bottles, and snack bags which are difficult to decompose and can pollute the environment including the oceans. Activities are carried out smoothly by the plans that have been prepared. Environmental management activities through efforts to clean up trash in the Mekongga Traditional House environment have been successfully carried out.